Border control: selectivity of chloroplast protein import and regulation at the TOC-complex - Demarsy, Emilie; Lakshmanan, Ashok M.; Kessler, Felix (Frontiers in Plant Science, 2014)
Plants have evolved complex and sophisticated molecular mechanisms to regulate their development and adapt to their surrounding environment. Particularly the development of their specific organelles, chloroplasts and other plastid-types, is finely tuned in accordance with the metabolic needs of the cell. The normal development and functioning of plastids require import of particular subsets of nuclear encoded proteins. Most preproteins contain a cleavable sequence at their N terminal (transit peptide) serving as a signal for targeting to the organelle and recognition by the translocation machinery TOC-TIC (Translocon of Outer membrane Complex, Translocon of Inner membrane Complex) spanning the dual membrane envelope. The plastid proteome needs constant remodeling in response to developmental and environmental factors. Therefore selective regulation of preprotein import plays a crucial role in plant development. In this review we describe the diversity of transit peptides and Toc receptor complexes, and summarize the current knowledge and potential directions for future research concerning regulation of the different Toc isoforms.